Alien plant species in the protected landscape area of the Odra river meanders: habitat preferences and threats - Koszela, Katarzyna; Tokarska-Guzik, Barbara (Biodiversity: Research and Conservation, 2008)
The protected landscape area of “The Odra River Meanders” is located in the south-west part of the province of Silesia, along the Odra river, on the border with the Czech Republic. This meandering fragment of the Odra river is one of the few places in Europe where natural geomorphological processes are still preserved. During botanical investigations, the occurrence of 363 vascular plant species was confirmed, including 95 species of alien origin. The participation of archaeophytes was 12%, kenophytes 10% and diaphytes 4%. A high participation of these groups of species was noted in habitats transformed by human activities, such as fields, roadsides and hedges, as well as in natural ones, such as steep escarpments and gravel sandbanks which have been shaped by the dynamic flow of the river. The first group of habitats was characterised by the highest proportion of archaeophytes, whereas in more natural habitats, the ascendancy of kenophytes (= neophytes) over older adventives was noted, e.g. the most common and widespread in this area were species from the Reynoutria (Fallopia) genus. The number of alien species in each habitat type was quite high and ranged from 1 to 62.